PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BILINGUAL MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED INSTRUCTION) PADA SUB POKOK BAHASAN PERSEGI PANJANG DAN PERSEGIKELAS VII - Rahmawati, Evi; Hobri, H; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2013)
Abstract.Problem Based Instruction is kind of learning model which introducing students to a real and meaningful problems. The phases of PBI are (1) orientating the students to a problem, (2) organizing the students to learn, (3) guiding the individual or group research, (4) developing and presenting the result, (5) analyzing and evaluating problem solving process. This research aims to develop the set of learning, such as syllabus, lesson plan, student book, student worksheet, and evaluation test by using Thiagarajan Model which consist of four steps such as define, design,develop, and disseminate. But this research just use the three of them, without disseminate step. SMP Negeri 3 Jember is elected as the research place. The coefficient validities of syllabus, lesson plan, student book, student worksheet, and evaluation test respectively are 0,975; 0,982; 0,984; 0,980; and 0,992. Since all of those coefficient more than 0,6, so we can conclude that the set of learning is valid and proper to be used. The reliability coefficient of evaluation test is 0,612717. Besides, the each item validity of evaluation test also showed a high number. There are five item problems where the coefficient validities of each number are 0,819533; 0,98036; 0,958226; 0,894288; and 0,960059. Key Words :Problem Based Instruction Learning Model, Thiagarajan, The Set of Learning, Validity, and Reliability.